The accurately digitized Dun Laoghaire Harbour marigram (sea level) records (1925-1931) - Patrick McLoughlin; Gerard D McCarthy; Glenn Nolan; Rosemarie Lawlor; Kieran Hickey (PANGAEA, 2024)
The case study of Dún Laoghaire Harbour in Ireland from 1925–1931 illustrates the challenges of accurately digitizing marigrams. The methodology involves digitizing the original marigram trace and the underlying grid at the nearest foot interval for each given hour to assess offsets. By subtracting the digitized foot interval from the known foot interval, differences are determined and then subtracted from each hourly trace value. This comparison between the original and adjusted data, where the upper and lower bounds were consistently aligned with the top line thickness during calibration, enhances the accuracy of final sea level data to the 10 mm level per year of data. The accompanying paper outlines the digitization and adjustment methodology, along with the compilation of key metadata. The attached metadata file in the dataset download explains the structure of the dataset, including its levels. The accurately digitized records from 1925 to 1931 can help us understand sea level changes over time.